Arab political reasoning: Muhammad Abid al-Jabiri’s contribution for understanding crisis of politics in the Arab world - Muhamad Rofiq (Indonesian Journal of Islam and Muslim Societies, 2017)
xt-stroke-width: 0px; " This paper deals with the thoughts of MuhammadAbid al-Jabiri (d. 2010), a prominent philosopher from Morocco, on the crisis of politics in the Arab world, by examining one of his great books entitled al-‘Aql al- Siyasi al-‘Arabi (Arab Political Reasoning). This book is the third work from the sequence Naqd al-‘Aql al-‘Arabi (Critique of Arab Reasoning). The Arab political reasoning here refers to a collection of motives (muhaddida t ) in politics and their theoretical and practical manifestations (tajalliyat ). This paper analyzes the sense of crisis that constitutes al-Jabiri’s thoughts on Arab political reasoning. This paper then describes the three theoretical frameworks he utilized, which were “aqidah (doctrine)”, “ghanimah (booty)” and “qabilah (tribe)”, and their application in the reading politics of the earliest period of Islamic history. Finally, this writing concludes with some points regarding al-Jabiri’s contribution to Islamic studies. 0px; " Tulisan ini mengkaji pemikiran-pemikiran Muhammad Abid al-Jabiri (w. 2010), seorang filosof terkemuka dari Maroko, mengenai krisis politik di dunia Arab, melalui pengkajian terhadap salah satu buku terkenalnya yang berjudulnya al-‘Aql al- Siyasi al-‘Arabi (Nalar Politik Arab). Buku ini adalah karya ketiga dari rangkaian proyek Naqd al-‘Aql al-‘Arabi (Kritik Nalar Arab). Nalar politik arab dalam karyanya ini terdiri dari sekumpulan motif-motif politik bangsa Arabdan manifestasi teoretis dan praktis dari motif tersebut. Tulisan ini selanjutnya menganalisis tiga latar belakang pemikiran yang membentuk ide-ide al-Jabiri mengenai nalar politik Arab. Tulisan ini kemudian menggambarkan tiga kerangka teori yang ia gunakan, yaitu akidah, harta rampasan perang, dan suku, serta aplikasi dari tiga teori tersebut pada pembacaan terhadap periode paling awal dari sejarah Islam. Terakhir, tulisan ini menyimpulkan sejumlah hal yang menjadi kontribusi al-Jabiri pada pemikiran keislaman.